WASTE REDUCTION AND CONTINUOUS IMPROVEMENT CULTURE: DETERMINANTS OF PERFORMANCE IN FOOD AND BEVERAGE MANUFACTURING FIRMS IN SOUTH-SOUTH NIGERIA (Journal of the Management Sciences, 2025)
This study investigates the effect of waste reduction and continuous improvement culture, two core components of the Integrated Lean Six Sigma (ILSS) production system on the performance of food and beverage manufacturing firms in South-South Nigeria. Anchored on the Theory of Constraints (TOC), the research examines how waste reduction influences production efficiency and how continuous improvement culture shapes employee productivity and engagement. A descriptive survey design was employed, with data collected from 303 respondents across five multinational food and beverage companies in the region. Data analysis involved descriptive statistics, linear regression, and multivariate analysis of variance (MANOVA). Findings reveal that waste reduction exerts a statistically significant positive effect on production efficiency (R = 0.784, R² = 0.615, p < .05), indicating that eliminating non-value-adding activities can improve efficiency by over 61%. Continuous improvement culture was also found to significantly influence both employee productivity (R² = 0.667) and employee engagement (R² = 0.536), underscoring the role of cultural transformation in workforce performance. The study concludes that adopting ILSS practices that integrate waste elimination and continuous improvement principles can enhance operational efficiency and workforce output in resource-constrained environments. It recommends that manufacturing firms should institutionalize continuous improvement programs, invest in employee training, and adopt data-driven waste reduction strategies to sustain long-term competitiveness.
Keywords: Lean Six Sigma; waste reduction; continuous improvement culture; production efficiency; employee productivity; Theory of Constraints